Analisis Pengaruh Jumlah Uang Beredar (JUB) Dan Tingkat Suku Bunga (RATE) Terhadap Inflasi Di Indonesia Tahun 2014-2023 - Budi Laksono; Vara Afrindasari; Zulfanah Diana; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of the Money Supply (JUB) and interest rates on inflation in Indonesia in the 2014-2023 period. The variables used are Inflation as the dependent variable, Money Supply (JUB) and Interest Rates as the independent variables. The data used in this research is secondary data obtained from publications by the Indonesian Central Bureau of Statistics. The analytical method used is a multiple linear regression model or Ordinary Least Square (OLS). In processing the data, the author used the help of Eviews 10 software. Based on the estimation results, it was found that there is a relationship between the Money Supply and Inflation in Indonesia and the Interest Rate variable has a positive and significant effect on Inflation in Indonesia.